FAIR GROUP NORMS AS A SOCIO-PSYCHOLOGICAL CRITERION OF A HEALTHY SPORTS ENVIRONMENT - Khvatskaya, E.E.; Korshunova, O.V.; Shtukkert, A.L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was a theoretical presentation of the “healthy sports environment” construct through environmental (material), hygienic, pedagogical and socio-psychological criteria, taking into account the type of difficulties / problems of athletes, as well as a partial empirical substantiation of the socio-psychological criterion through the identification of typical rules of a sports group / teams and assessing the appropriateness of fair group norms (hereinafter referred to as FGN) in the real conditions of sports activities. Methods and structure of the study. Theoretical analysis of literature; method of incomplete sentences for determining typical norms in sports “The rules of the group/team that were in my sports career are…” (at least three) with the participation of ex-athletes of different sports (n=138, men – 75, women – 63, age 21 – 32); content analysis; the feasibility and effectiveness of the development of the FGN was assessed in several teams in St. Petersburg in 2021-2022. in the form of a pilot experiment. Research results and conclusions. An approach to the definition of the construct "healthy sports environment" in the narrow and broad senses is proposed. A typical number of group rules in a sports career among respondents, the predominance of rules of an organizational nature and their negative formulations (more often they begin with “not” and “not”), and stereotypes are noted. Most of the rules do not correspond to the signs of fair group norms. The conditions for the development of fair group norms for athletes/teams are indicated. The feasibility and effectiveness of the development of FGN was determined when working with several teams in St. Petersburg in 2021-2022.